KNOWLEDGE AND PRACTICE OF RABIES PREVENTION AMONG PEOPLE WHO COME TO GET VACCINATED AGAINST RABIES AT THE HAU GIANG PROVINCIAL CENTER FOR DISEASE CONTROL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the status of knowledge and practice regarding rabies prevention among people coming to get rabies vaccines at the Hau Giang provincial Center for Disease Control in 2025.Methods: A cross-sectional descriptive study was conducted on 370 people coming to get rabies vaccines at the Hau Giang provincial Center for Disease Control.Results: The results showed that the rate of subjects with adequate general knowledge of rabies prevention was 68.1%. The rate of correct general practice regarding rabies prevention was very high, at 95.4%.Conclusion: The high practice rate reflects the characteristic of the study subjects, who had already proactively come to the health center for vaccination. However, the fact that nearly one-third of subjects still lacked adequate knowledge (30.3%) indicates the need to strengthen direct counseling at health facilities to fill this knowledge gap.
Keywords: Rabies, knowledge, practice, prevention.